PEMBINAAN MUALLAF MELALUI KEGIATAN KULIAH KERJA LAPANGAN (KKL) DI DUSUN MANJAU DESA LAMAN SATONG KECAMATAN MATAN HILIR UTARAKABUPATEN KETAPANG - Iwan Iwan; M. Hafidz Al-Gifari, Amar Ad Dzurori, Bahrul Ilmi, Rafita, Evi, Lastari (Adiba Aisha Amira, 2024)
This study aims to describe the forms, processes, and impacts of muallaf (convert to Islam) development carried out through the Field Work Lecture (Kuliah Kerja Lapangan or KKL) activities in Dusun Manjau, Laman Satong Village, North Matan Hilir District, Ketapang Regency. The development program was conducted in five main forms: personal mentoring, Islamic studies, Qur’an reading courses, religious consultations, and development through silaturahmi (social visits). The research method used is qualitative descriptive, with data collection techniques including observation, interviews, and documentation. The results show that personal mentoring plays a crucial role in building emotional closeness and spiritual motivation among the muallaf. Islamic studies and Qur’an reading courses help improve understanding and worship skills. Religious consultations provide space for muallaf to express the problems they face, while silaturahmi activities strengthen social bonds between muallaf and the local Muslim community. Overall, the KKL activities significantly contribute to the strengthening of faith, worship skills, and the social integration of muallaf in their new environment.